Measuring Threshold Potentials of Neuron Cells Using Hodgkin-Huxley Model by Applying Different Types of Input Signals (Dhaka University Journal of Science, 2016)
The Hodgkin-Huxley model is the first successful mathematical model for explaining the initiation and propagation of an action potential in a neuron cell. In this paper we reinvestigated the Hodgkin-Huxley model through computer simulation and determined the threshold potentials by applying different types of stimulating input signals. To implement the work, a computer programme of the Hodgkin-Huxley model was written in MATLAB programming language. The action potentials of neuron cells were checked and the threshold potentials of the neuron cell for specific types of stimulating input signals were tabulated with an aim to utilize these values to do experiment on neuron cell in future.Dhaka Univ. J. Sci. 64(1): 15-20, 2016 (January)